Potensi Kulit Ubi Kayu (Manihot Esculenta) di Kecamatan Koto Xl Tarusan sebagai Sumber Karbon untuk Material Maju - Wini Andriani; Umar Kalmar Nizar (Jurnal Periodic Jurusan Kimia UNP, 2023)
The purpose of this research is the optimal carbonization temperature, to obtain economical, environmentally friendly and quality carbon from cassava peel waste. Cassava peel carbon is synthesized through a carbonization process. The method used to manufacture carbon from cassava peel is by calcining it in a furnace at various temperatures of 250℃, 350℃, and 450 for 1 hour. The carbon obtained was tested for ash content, vapor content and bound carbon. In this study, the standard used to determine the characteristics of the carbon produced is the Indonesian National Standard (SNI 06-3730-1995). The results showed that the optimal carbonization temperature for cassava peel carbon was 250℃, where the ash content was 7.14%, the vapor content was 5.32% and the bound carbon was 87.54%. Based on these results, it can be concluded that cassava peel waste can be used as carbon that meets the Indonesian National Standard (SNI 06-3730-1995).